Self-layering anti-corrosion hydrophilic coating and application thereof

By using hydrophilic acrylic resin and polyetheramine-modified epoxy resin composite graphene materials and other coatings, the anti-corrosion and hydrophilic functions of the aluminum fins of the air-conditioning heat exchanger are realized at one time, solving the complexity and quality problems of multi-layer coatings in the prior art, and improving the stability and corrosion resistance of the coating.

CN119735986APending Publication Date: 2025-04-01GUANGDONG RUIHE NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411914374.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

Smart Images

  • Figure CN119735986A_ABST
    Figure CN119735986A_ABST
Patent Text Reader

Abstract

The invention provides a self-stratifying anti-corrosion hydrophilic coating and application, and belongs to the technical field of anti-corrosion hydrophilic coatings. The self-stratified anticorrosive hydrophilic coating is formed by mixing hydrophilic acrylic resin, a polyether amine modified epoxy resin composite graphene material, waterborne polyurethane resin, amino resin, a closed acid catalyst, a cosolvent and additives, wherein the additives comprise a flatting agent and a defoaming agent. According to the self-layering anti-corrosion hydrophilic coating, self-layering can be achieved during curing, the hydrophilic function and the anti-corrosion function can be achieved only through one-time coating, compared with an existing multi-layer coating process, the coating process is greatly simplified, the production efficiency is improved, all layers are tightly combined through the self-layering structure, and the self-layering anti-corrosion hydrophilic coating is good in anti-corrosion performance and good in anti-corrosion performance. The problem of layering and stripping is effectively avoided, so that the stability of the coating is improved. The coating disclosed by the invention not only has hydrophilic and anti-corrosion functions, but also endows the coating with certain heat-conducting property by the graphene oxide in the raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion hydrophilic coatings, in particular to a self-stratified anti-corrosion hydrophilic coating and its application. Background Art

[0002] Air conditioners are extremely popular in modern daily life, and their core components, heat exchangers, are evolving towards miniaturization and lightweight. This development trend has led to a continuous reduction in the spacing between the aluminum fins of the heat exchanger. As the spacing between the aluminum fins decreases, the water vapor condensed between the fins is prone to form a "water bridge". This phenomenon occurs because when the spacing becomes smaller, the small water droplets condensed by water vapor are more likely to connect with each other to form a structure that hinders the airflow, thereby increasing the air resistance of the air conditioner and ultimately affecting the heat exchange efficiency of the heat exchanger. In addition, the aluminum fins of the air conditioner heat exchanger are prone to corrosion. Especially in some special environments, such as air conditioners in highly corrosive environments such as large ships or marine environments, due to the high salt content and high humidity in the air, these salt spray and water vapor are easily attached to the aluminum fins of the air conditioner heat exchanger, and the aluminum fins are in a wet state when the air conditioner is working and in a dry state when it is stopped. This alternating state of dry and wet further increases the risk of corrosion of the aluminum fins. Seriously shortening the service life of the heat exchanger. To solve these problems, currently, applying a hydrophilic coating on the surface of aluminum foil used for heat exchange in air conditioners is an effective solution. That is, a hydrophilic coating is applied on the surface of the aluminum foil of the aluminum fin to form a hydrophilic coating film, allowing condensed water to spread and flow away quickly on its surface, thereby solving the "water bridge" problem. At the same time, the surface of the aluminum foil also needs to be treated with anti-corrosion to simultaneously solve the problem of aluminum fins being easily corroded.

[0003] Among the existing technologies for aluminum foil coatings for heat exchangers, there is the use of modified graphene oxide and then introduced into the coating to achieve the super anti-corrosion function. For example, patent CN111205727A discloses a water-based super anti-corrosion coating for aluminum fins of air-conditioning heat exchangers. The coating uniformly disperses graphene oxide (GO) modified with styryltrimethoxysilane in acrylic monomers in the form of in-situ polymerization, and uses the active groups on its surface as initiators. Acrylic monomers are polymerized on its surface to obtain graphene oxide / water-soluble acrylic resin, and a water-based super anti-corrosion coating is prepared using this as the base material. The prepared water-based super anti-corrosion coating has excellent adhesion, mechanical properties, super long corrosion resistance, and better heat dissipation function. However, this technology uses styryltrimethoxysilane-modified graphene oxide, which has poor hydrophilic properties, and the technology does not disclose the hydrophilic properties of its coating, making it difficult to apply to fins with smaller spacing; there are also schemes using two layers of coating, such as patent CN105602376A discloses a graphene-modified aluminum foil hydrophilic coating, which disperses graphene powder in a solvent under magnetic field and ultrasonic conditions, and sequentially adds silver nanopowder, titanium dioxide nanopowder, acrylic resin and additives. The hydrophilic aluminum foil is obtained by applying a primer and then applying the graphene-modified aluminum foil hydrophilic coating on the clean aluminum foil surface. The coating and the hydrophilic aluminum foil prepared using the coating have stable, long-lasting and uniform antibacterial properties, mildew and anticorrosion functions, and higher thermal conductivity. However, this technology requires two coatings to obtain an anticorrosive hydrophilic coating, which is cumbersome to operate and prone to quality problems between coatings. At present, a bottom-to-bottom integrated solution is adopted, such as patent CN102719188A discloses a bottom-to-bottom integrated hydrophilic aluminum foil coating, which is cured into a film by ultraviolet irradiation. The preparation of the hydrophilic acrylic resin in its components is obtained by synthesizing an acrylic resin by a solution polymerization method and then adding diethanolamine thereto to neutralize and form a salt. After weighing and mixing each component in proportion, mechanical stirring is uniform to obtain a bottom-to-bottom integrated hydrophilic aluminum foil coating. After the paint film of the present invention is cured, the coating has strong continuous hydrophilicity, moderate hardness, good adhesion, and less wear on the punching mold. The coating provides anticorrosion, protection, and hydrophilic effects on the aluminum foil. Although this technology solves the drawbacks of two-coating, its corrosion resistance is poor, and its salt spray performance can only reach 72 hours, which is difficult to apply to special environments; for example, patent CN108395770A discloses an anti-corrosion hydrophilic coating containing chlorinated natural rubber, which can spontaneously form a hydrophobic anti-corrosion bottom layer and a hydrophilic top layer after one coating, and the performance of each coating is naturally transitioned, and the adhesion between the coatings is high. Although this coating not only solves the construction problem of multiple coatings and has hydrophilicity and high anti-corrosion performance, the raw materials of the coating use chlorinated rubber and various fillers, and its thermal conductivity is relatively low, which will reduce the heat exchange efficiency of the aluminum foil of the heat exchanger and increase energy consumption. Summary of the invention

[0004] The purpose of the present invention is to provide a self-stratified anti-corrosion hydrophilic coating and its application in view of the above-mentioned problems in the prior art.

[0005] The purpose of the present invention can be achieved by the following technical scheme: a self-stratified anti-corrosion hydrophilic coating, the raw materials of the self-stratified anti-corrosion hydrophilic coating include hydrophilic acrylic resin, polyetheramine modified epoxy resin composite graphene material, waterborne polyurethane resin, amino resin, blocked acid catalyst, cosolvent and additives, the additives include leveling agent and defoamer; according to the weight ratio, hydrophilic acrylic resin: polyetheramine modified epoxy resin composite graphene material: waterborne polyurethane resin: amino resin: blocked acid catalyst: cosolvent: additive is 30-50:10-20:5-15:15-30:1-3:3-8:1-5,

[0006] The hydrophilic acrylic resin is prepared by free radical copolymerization of methyl methacrylate, ethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and acrylic acid, wherein the weight ratio of methyl methacrylate: ethyl acrylate: hydroxypropyl acrylate: hydroxyethyl methacrylate: acrylic acid is 3-8:1-5:2-6:2-6:1

[0007] The specific method for preparing the polyetheramine-modified epoxy resin composite graphene material is as follows: firstly, polyetheramine is added dropwise into an aqueous epoxy resin liquid, a ring-opening reaction occurs between the polyetheramine and the aqueous epoxy resin to obtain an aqueous polyetheramine-modified epoxy resin, and then a covalent bond coupling reaction occurs between the aqueous polyetheramine-modified epoxy resin and graphene oxide in a graphene oxide dispersion to obtain a polyetheramine-modified epoxy resin composite graphene material; the aqueous epoxy resin is selected from a bisphenol A type aqueous epoxy resin or an aliphatic aqueous epoxy resin; and according to the weight ratio, the polyetheramine: aqueous epoxy resin: graphene oxide is 18-42:15-35:1.

[0008] Preferably, the blocked acid catalyst is one of p-toluenesulfonic acid, dinonylnaphthalene disulfonic acid and dodecylbenzenesulfonic acid; the cosolvent is at least one of propylene glycol methyl ether, ethylene glycol methyl ether, ethylene glycol butyl ether, ethanol and propylene glycol; the leveling agent is an organosilicon leveling agent, and the defoaming agent is a polyether defoaming agent.

[0009] Preferably, in the free radical copolymerization reaction, ammonium persulfate is selected as the initiator and sodium dodecyl sulfate is selected as the surfactant.

[0010] Preferably, the polyetheramine is one of Jeffamine D-400 polyetheramine, Jeffamine XTJ-500 polyetheramine and Jeffamine ED-600 polyetheramine, and the speed of dropping the polyetheramine is 1.8-4.2 g / min.

[0011] The waterborne polyurethane resin is one of Bayhydrol UH 2697 waterborne polyurethane resin, Bayhydrol UH 245 waterborne polyurethane resin and Bayhydrol UH 2891 waterborne polyurethane resin; in the present anticorrosive hydrophilic coating technology system, the waterborne polyurethane resin can promote the densification of the coating structure, effectively maintain the integrity of the entire coating structure and the stability of the coating.

[0012] The amino resin is one of CYMEL 325 amino resin, CYMEL 385 amino resin and ETERMINO 9223-60 amino resin.

[0013] The silicone leveling agent is one of Deqian 435 leveling agent, Deqian 410 leveling agent and Deqian 432 leveling agent; the defoaming agent is one of DAPRO AP 7010 defoaming agent, DAPRO DF 696 leveling agent and DF7015 leveling agent.

[0014] Preferably, for the free radical copolymerization reaction, the conditions are set as follows: temperature is 60-85° C., and time is 6-10 hours.

[0015] Preferably, for the ring-opening addition reaction, the conditions are set as follows: temperature is 50-85° C., and time is 2-8 h.

[0016] Preferably, the specific process for preparing the graphene oxide dispersion is as follows: graphene oxide, deionized water and a dispersant are uniformly mixed to obtain an initial graphene oxide dispersion, the initial graphene oxide dispersion is subjected to ultrasonic dispersion treatment to obtain a graphene oxide dispersion, and the dispersant is one of BYK-190, BYK-153 and BYK-2012.

[0017] The invention discloses an application of a self-stratified anti-corrosion hydrophilic coating, wherein the self-stratified anti-corrosion hydrophilic coating is coated on an aluminum foil sheet of a heat exchanger.

[0018] Preferably, the dry film thickness after coating is 1-3 μm.

[0019] The technical solution of the present invention can realize the self-stratification function of the coating through the difference in physical properties between the raw materials. When the coating is applied to the aluminum substrate and begins to solidify, the components in the coating are affected by the surface energy difference and gravity, and self-stratification occurs. The polyetheramine-modified epoxy resin composite graphene material will migrate toward the direction close to the substrate due to gravity and relatively high surface energy. Since the polyetheramine has modified the epoxy resin, this modification improves the flexibility of the epoxy resin and the adhesion to the substrate. At the same time, the epoxy resin itself has good anti-corrosion properties and can form a protective layer between the coating and the substrate to block the corrosive medium. After the graphene oxide is composited with the modified epoxy resin, it is also migrated to the surface of the substrate, thereby being closely combined with the substrate. Its lamellar structure can effectively block the penetration of the corrosive medium, further enhancing the anti-corrosion ability of the coating. The hydrophilic acrylic resin in the coating migrates to the surface of the coating. Its hydrophilicity comes from the various monomers copolymerized by the resin. Some monomers have hydrophilic functional groups such as hydroxyl and carboxyl, which can form hydrogen bonds with water molecules. The presence of a large number of hydrogen bonds enables the coating surface to attract and bind water molecules, thus presenting hydrophilicity. Finally, the presence of amino resins and waterborne polyurethane resins in the coating can cross-link with other resins to make the coating structure dense, thus forming a coating that is both anti-corrosive and hydrophilic.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The self-stratifying anti-corrosion hydrophilic coating of the present invention is applied on the aluminum foil of the heat exchanger for protection. It can realize self-stratification during curing, and can achieve the dual functions of hydrophilicity and anti-corrosion with only one coating, without multiple coatings. Compared with the existing multi-layer coating process, it greatly simplifies the coating process and improves production efficiency. In addition, the self-stratifying structure makes the layers tightly combined, effectively avoiding the problem of stratification and peeling, thereby improving the stability of the coating and extending the service life of the coating.

[0022] 2. The polyetheramine modified epoxy resin composite graphene material prepared by the present invention can not only self-stratify to the surface of the substrate when the coating is cured, but also enhance the anti-corrosion effect of the coating. Its own characteristics also give the coating a certain thermal conductivity. In the application scenario of the heat exchanger, good thermal conductivity helps the transfer of heat, while excellent anti-corrosion performance can extend the service life of the heat exchanger. At the same time, the coating integrates anti-corrosion and hydrophilic functions. While meeting the anti-corrosion and hydrophilic requirements, it will not cause any adverse effects on the heat exchange performance of the aluminum foil of the heat exchanger, which is critical, ensuring that the heat exchanger can perform heat exchange work normally and efficiently while having good protective performance.

[0023] 3. The present invention optimizes the raw materials of the coating, which helps the raw materials to cooperate with each other. Through the self-stratification of polyetheramine-modified epoxy resin composite graphene material and hydrophilic acrylic resin, anti-corrosion and hydrophilic properties are achieved, and water-based polyurethane resin and amino resin can improve the overall performance of the coating, and together with other raw materials, a coating system with excellent performance is constructed. The coating is easy to operate during coating, which can reduce production costs and improve production efficiency, which has positive significance for the large-scale promotion and application of the coating in practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The infrared spectra of the polyetheramine-modified epoxy resin composite graphene material and the polyetheramine-modified epoxy resin in Example 1;

[0025] Among them, No. 1 is a polyetheramine modified epoxy resin composite graphene material, and No. 2 is a polyetheramine modified epoxy resin. DETAILED DESCRIPTION

[0026] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0027] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0028] The room temperature mentioned in the examples or comparative examples of the present invention is 25°C.

[0029] The graphene oxide used in the examples or comparative examples of the present invention was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a model number of XF002-2.

[0030] The aqueous epoxy resin used in the examples or comparative examples of the present invention is bisphenol A epoxy resin, model CYDW-100.

[0031] The contact angle measuring instrument used in the embodiments or comparative examples of the present invention is a JGW-360B.

[0032] Example 1

[0033] A self-stratified anticorrosive hydrophilic coating is composed of the following raw materials in parts by weight: 45 parts of hydrophilic acrylic resin, 16 parts of polyetheramine modified epoxy resin composite graphene material, 8 parts of waterborne polyurethane resin Bayhydrol UH 245, 20 parts of amino resin CYMEL 325, 2 parts of p-toluenesulfonic acid, 6 parts of propylene glycol, 2 parts of leveling agent Deqian 435 and 2 parts of defoaming agent DF7015.

[0034] The preparation process of the anticorrosive hydrophilic coating in this embodiment is as follows:

[0035] Preparation of polyetheramine modified epoxy resin composite graphene material: 5 parts of graphene oxide were added to 300 parts of deionized water and 0.4 parts of BYK-190, and put into an ultrasonic disperser, and the ultrasonic frequency was set to 40kHz for ultrasonic treatment for 45 minutes, and a 2-minute pause was made every 15 minutes to prepare a graphene oxide dispersion for use; then 100 parts of water-based epoxy resin were added to a four-necked flask, 15 parts of propylene glycol methyl ether and 50 parts of deionized water were added, and the stirrer was turned on and set to a stirring speed of 400rpm and a temperature of 35°C for stirring for 30 minutes, and then 125 parts of polyetheramine Jeffamine D-400 was added dropwise at a rate of 2 g / min. After the addition was completed, the reaction temperature was set to 70°C, the reaction time was 6 hours, and the stirring speed was 400 rpm for a ring-opening addition reaction. After the reaction was completed, it was naturally cooled to room temperature to obtain an aqueous polyetheramine-modified epoxy resin. The graphene oxide dispersion prepared above was then added dropwise at a rate of 5 ml / min. During the addition, the heating and agitator were turned on with a stirring speed of 600 rpm and a temperature of 50°C. After the addition was completed, the stirring reaction was continued for 3 hours for a coupling reaction to obtain a polyetheramine-modified epoxy resin composite graphene material.

[0036] Preparation of hydrophilic acrylic resin: prepare 146 parts of monomer mixture, including 48 parts of methyl methacrylate, 36g of ethyl acrylate, 25g of hydroxypropyl acrylate, 25g of hydroxyethyl methacrylate, 12g of acrylic acid, and also prepare 1.2g of ammonium persulfate and 2.5g of sodium dodecyl sulfate. First, add 61 parts of deionized water and 2.5 parts of sodium dodecyl sulfate into a reactor, stir to fully dissolve them, then slowly drop 30 parts of mixed monomers, keep the reactor temperature at 25°C during dropwise addition, continue stirring for 1 hour after dropwise addition to form a stable pre-emulsion, then heat the reactor to 70°C and add 0.4 parts of ammonium persulfate and 23.3 parts of water, slowly drop the remaining 116 parts of mixed monomers and the remaining 0.8 parts of ammonium sulfate after seeing blue fluorescence in the reaction system, control the dropwise addition time to 2.5h and keep the reaction temperature at 70°C, continue the reaction for 8 hours after dropwise addition to ensure complete monomer reaction, cool to room temperature after the reaction is completed, and adjust the pH value to 7-8 with ammonia water to obtain an aqueous hydrophilic acrylic resin emulsion.

[0037] Preparation of anti-corrosion hydrophilic coating: Mix the hydrophilic acrylic resin, polyetheramine-modified epoxy resin composite graphene material, Bayhydrol UH 245, CYMEL 325, p-toluenesulfonic acid, propylene glycol, leveling agent Deqian 435 and defoaming agent DF7015 in sequence and evenly.

[0038] Example 2

[0039] Compared with Example 1, the only difference is that the raw materials and proportions of the anti-corrosion hydrophilic coating are different, and the other conditions and steps are the same. The proportions of the anti-corrosion hydrophilic coating in this embodiment are: 48 parts of hydrophilic acrylic resin, 13 parts of polyetheramine modified epoxy resin composite graphene material, 14 parts of water-based polyurethane resin Bayhydrol UH 2891, 22 parts of amino resin CYMEL 385, 3 parts of toluenesulfonic acid, 4 parts of propylene glycol, 2 parts of leveling agent Deqian 435 and 2 parts of defoaming agent DF7015.

[0040] Example 3

[0041] Compared with Example 1, the only difference is that the mass ratio of polyetheramine, water-based epoxy resin and graphene oxide is changed to 30:25:1, and the other conditions and steps are the same.

[0042] Example 4

[0043] Compared with Example 1, the only difference is that the mass ratio of methyl methacrylate, ethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and acrylic acid in the preparation process of the hydrophilic acrylic resin is changed to 3:4:2.5:2.5:1, and the other conditions and steps are the same.

[0044] Example 5

[0045] Compared with Example 1, the only difference is that the conditions of the ring-opening addition reaction are: temperature of 55° C. and time of 8 h, and the other conditions and steps are the same.

[0046] Comparative Example 1

[0047] Compared with Example 1, the only difference is that the anti-corrosion hydrophilic coating of this comparative example does not add the polyetheramine modified epoxy resin composite graphene material, but directly adds the graphene oxide dispersion, and the other conditions and steps are the same. The raw materials of the coating of this comparative example are as follows: 45 parts of hydrophilic acrylic resin, 9 parts of graphene oxide dispersion, 8 parts of waterborne polyurethane resin Bayhydrol UH245, 20 parts of amino resin CYMEL 325, 2 parts of p-toluenesulfonic acid, 6 parts of propylene glycol, 2 parts of leveling agent Deqian 435 and 2 parts of defoaming agent DF7015.

[0048] Comparative Example 2

[0049] Compared with Example 1, the only difference is that the graphene oxide and the waterborne polyetheramine modified epoxy resin are not subjected to coupling reaction, but only physical mixing is performed, and the other conditions and steps are the same. The raw materials of this comparative example are as follows: 45 parts of hydrophilic acrylic resin, 7 parts of polyetheramine modified epoxy resin, 9 parts of graphene oxide dispersion, 8 parts of waterborne polyurethane resin Bayhydrol UH245, 20 parts of amino resin CYMEL 325, 2 parts of p-toluenesulfonic acid, 6 parts of propylene glycol, 2 parts of leveling agent Deqian 435 and 2 parts of defoaming agent DF7015.

[0050] Comparative Example 3

[0051] Compared with Example 1, the only difference is that no water-based polyurethane resin is added, and the other conditions and steps are the same. The coating of this comparative example is composed of the following raw materials in parts by weight: 49 parts of hydrophilic acrylic resin, 20 parts of polyetheramine modified epoxy resin composite graphene material, 8 parts of water-based polyurethane resin Bayhydrol UH 245, 20 parts of amino resin CYMEL 325, 2 parts of p-toluenesulfonic acid, 6 parts of propylene glycol, 2 parts of leveling agent Deqian 435 and 2 parts of defoaming agent DF7015.

[0052] Comparative Example 4

[0053] Compared with Example 1, the only difference is that no graphene oxide dispersion is added, the polyetheramine-modified epoxy resin composite graphene material is changed to polyetheramine-modified epoxy resin, and the other conditions and steps are the same.

[0054] Comparative Example 5

[0055] Compared with Example 1, the only difference is that the epoxy resin is not modified, and the polyetheramine-modified epoxy resin composite graphene material is replaced by epoxy resin, and the other conditions and steps are the same.

[0056] Comparative Example 6

[0057] Compared with Example 1, the only difference is that the epoxy resin is not modified with polyetheramine but directly modified with graphene oxide by coupling reaction, and the other conditions and steps are the same.

[0058] like Figure 1As shown, it can be seen from the infrared spectrum that the peak at 2956.9cm-1 in the No. 2 polyetheramine modified epoxy resin is the aliphatic-CH stretching vibration peak, which is the characteristic peak of the alkyl group in the polyetheramine, the peaks at 1043.4cm-1 and 1163.3cm-1 are the stretching vibration peaks of COC, which are the characteristic peaks of the epoxy group in the epoxy resin, and the characteristic peak around 1650.9cm-1 is the stretching vibration peak of CO-NH. The appearance of these characteristic peaks indicates that the preparation of the polyetheramine modified waterborne epoxy resin is successful. In the polyetheramine modified epoxy resin composite graphene material, a new characteristic peak appears at 1090.9cm-1, indicating that a new CO-related vibration peak appears in the material, which is related to the CO bond formation involved in the coupling reaction between graphene oxide and polyetheramine modified epoxy resin, which also indicates that graphene oxide has successfully reacted with polyetheramine modified epoxy resin.

[0059] The coatings prepared in Examples 1-5 and Comparative Examples 1-6 were coated on aluminum foil by roller coating and then baked at 280°C for 30s to obtain test samples, and the dry film thickness was controlled to be 1-3 μm. Each test aluminum foil sample was tested, and the results are shown in Table 1. The specific test methods and standards are as follows:

[0060] Initial hydrophilic angle: The angle of the first drop of water on the test sample is measured using a contact angle meter.

[0061] Process hydrophilic angle: Soak the sample in fin oil Rf190 for 48 hours, bake it at 150°C for 10 minutes, and measure the angle with a contact angle meter. If it is greater than 12°, it is unqualified.

[0062] Adhesion: Test method refer to GB / T9286-1998.

[0063] Appearance: Observe whether the coating is smooth and has no abnormalities.

[0064] Wet-dry cycle angle: Soak the sample in pure water for 2 minutes, then lift it up and air dry it for 6 minutes. This is one cycle. After 300 consecutive cycles, use a contact angle meter to measure the angle. If it is greater than 26°, it is unqualified.

[0065] Solvent resistance: Use gauze dipped in butanone to wipe the sample back and forth. After wiping 30 times, rinse with clean water and air dry. Then use a contact angle meter to measure the angle. If it is greater than 20°, it is unqualified.

[0066] Alkali resistance: Soak in 10% NaOH at 25°C for 10 minutes, then rinse with clean water and observe the corrosion condition.

[0067] Salt spray resistance: The test method refers to JISZ2371-2000, and the rating is carried out after 2000h of testing.

[0068] Table 1 Performance test results of Examples 1-5 and Comparative Examples 1-3:

[0069] Table 1 Performance test results of Examples 1-5 and Comparative Examples 1-3

[0070]

[0071]

[0072] As can be seen from Table 1, the performances obtained by testing the technical solution of the present invention in Examples 1-5 are all qualified, the initial hydrophilic angles are all below 6°, the alkali resistance and solvent resistance are all qualified, and especially the salt resistance can still maintain level 10 after being tested for 2000h, indicating that the anti-corrosion hydrophilic coating prepared by the present invention can achieve both hydrophilic and anti-corrosion functions in only one coating. In Comparative Example 1, the coating formula does not contain polyetheramine-modified epoxy resin, but directly contains graphene oxide dispersion. It can be seen that the performances are not ideal, and black spots appear in the coating, which is estimated to be caused by the appearance of graphene oxide in the system. Agglomeration is caused. From the test results of Comparative Example 1, it can be seen that without adding polyetheramine-modified epoxy resin, even if the coating system contains hydrophilic acrylic resin, its hydrophilicity is still poor. This is mainly because the coating does not show self-stratification during curing, resulting in the failure of graphene oxide in the coating to migrate to the substrate, but dispersed throughout the coating, resulting in a significant decrease in hydrophilicity; in the coating formula of Comparative Example 2, even if polyetheramine-modified epoxy resin is added but not coupled with graphene oxide, its coating still has black spots, and the hydrophilicity is still poor, and the alkali resistance and salt spray resistance are poor. Although the performance is better than that of the scheme in comparative example 1, it is still inferior to that of the schemes in embodiments 1-5, mainly because the polyetheramine-modified epoxy resin has poor self-stratification effect when it is not covalently coupled with graphene oxide, resulting in the failure of graphene oxide to completely migrate to the bottom layer; in comparative example 3, the raw material does not add water-based polyurethane resin, and it can be seen that the corrosion resistance of its coating is poor, and the prepared coating is easy to stratify and has poor stability; in comparative example 4, no graphene oxide is added, and it can be seen from the results that the hydrophilicity of its coating is qualified, but its corrosion resistance is poor; in comparative example 5, the epoxy resin is not modified, It can be seen from the test results that the performance is relatively poor, especially the corrosion resistance and alkali resistance are extremely poor, mainly because there is no physical shielding of the substrate by the graphene sheet layer, and the invasion of corrosive media cannot be effectively prevented; although comparative example 6 uses graphene oxide to graft and modify the epoxy resin, the corrosion resistance of its coating is still worse than that of embodiments 1-5, mainly because the epoxy resin modified by polyetheramine is not used, and an effective cross-linked network structure cannot be formed to enhance the density of the coating, especially the combination with the acrylic resin migrated to the top is not tight enough, and it is impossible to form an effective protective network as in the embodiments.

[0073] In summary, the present invention provides a self-stratified anti-corrosion hydrophilic coating, which can achieve self-stratification during curing, and can achieve the dual functions of hydrophilicity and anti-corrosion with only one coating. Compared with the existing multi-layer coating process, this greatly simplifies the coating process and improves production efficiency. And this self-stratified structure makes the layers tightly combined, effectively avoiding the problem of stratification and peeling, thereby improving the stability of the coating. The coating not only has the functions of hydrophilicity and anti-corrosion, but the graphene oxide in the raw material also gives the coating a certain thermal conductivity. In the application scenario of the heat exchanger, good thermal conductivity helps the transfer of heat. While meeting the requirements of anti-corrosion and hydrophilicity, it will not cause any adverse effects on the heat exchange performance of the heat exchanger aluminum foil, which is crucial, ensuring that the heat exchanger can perform heat exchange work normally and efficiently while having good protective performance.

[0074] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A self-stratified anticorrosive hydrophilic coating, characterized in that: The raw materials for forming the self-stratified anti-corrosion hydrophilic coating include hydrophilic acrylic resin, polyetheramine modified epoxy resin composite graphene material, waterborne polyurethane resin, amino resin, blocked acid catalyst, cosolvent and additives, and the additives include leveling agent and defoamer; according to the weight ratio, the hydrophilic acrylic resin: polyetheramine modified epoxy resin composite graphene material: waterborne polyurethane resin: amino resin: blocked acid catalyst: cosolvent: additive is 30-50:10-20:5-15:15-30:1-3:3-8:1-5.

2. The self-stratifying anticorrosive hydrophilic coating according to claim 1, characterized in that: The hydrophilic acrylic resin is prepared by free radical copolymerization of methyl methacrylate, ethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and acrylic acid, wherein the weight ratio of methyl methacrylate: ethyl acrylate: hydroxypropyl acrylate: hydroxyethyl methacrylate: acrylic acid is 3-8:1-5:2-6:2-6:

1.

3. The self-stratifying anticorrosive hydrophilic coating according to claim 1, characterized in that: The specific steps of preparing the polyetheramine-modified epoxy resin composite graphene material are as follows: firstly, polyetheramine is added dropwise into an aqueous epoxy resin liquid, a ring-opening reaction is performed between the polyetheramine and the aqueous epoxy resin to obtain an aqueous polyetheramine-modified epoxy resin, and then a covalent bond coupling reaction is performed between the aqueous polyetheramine-modified epoxy resin and graphene oxide in a graphene oxide dispersion to obtain a polyetheramine-modified epoxy resin composite graphene material; the aqueous epoxy resin is selected from bisphenol A type aqueous epoxy resin or aliphatic aqueous epoxy resin; and according to the weight ratio, the polyetheramine: aqueous epoxy resin: graphene oxide is 18-42:15-35:

1.

4. The self-stratifying anticorrosive hydrophilic coating according to claim 1, characterized in that: The closed acid catalyst is one of p-toluenesulfonic acid, dinonylnaphthalene disulfonic acid and dodecylbenzenesulfonic acid; the cosolvent is at least one of propylene glycol methyl ether, ethylene glycol methyl ether, ethylene glycol butyl ether, ethanol and propylene glycol; the leveling agent is an organic silicon leveling agent, and the defoaming agent is a polyether defoaming agent.

5. The self-stratifying anticorrosive hydrophilic coating as claimed in claim 2, characterized in that: In the free radical copolymerization reaction, ammonium persulfate is selected as the initiator and sodium dodecyl sulfate is selected as the surfactant; The rate of adding polyetheramine is 1.8-4.2 g / min; For the free radical copolymerization reaction, the conditions are set as follows: temperature is 60-85°C, and time is 6-10 hours.

6. The self-stratifying anticorrosive hydrophilic coating as claimed in claim 3, characterized in that: For the ring-opening addition reaction, the conditions are set as follows: temperature is 50-85°C, and time is 2-8h.

7. The self-stratifying anticorrosive hydrophilic coating according to claim 1, characterized in that: For the graphene oxide dispersion, the specific preparation process is as follows: graphene oxide, deionized water and a dispersant are evenly mixed to obtain an initial graphene oxide dispersion, the initial graphene oxide dispersion is subjected to ultrasonic dispersion treatment to obtain a graphene oxide dispersion, and the dispersant is one of BYK-190, BYK-153 and BYK-2012.

8. An application of a self-stratifying anti-corrosion hydrophilic coating, wherein the self-stratifying anti-corrosion hydrophilic coating is the self-stratifying anti-corrosion hydrophilic coating according to any one of claims 1 to 7, characterized in that: The self-stratified anti-corrosion hydrophilic coating is applied on the aluminum foil of the heat exchanger.

9. The use of the self-stratified anticorrosive hydrophilic coating as claimed in claim 8, characterized in that: The dry film thickness of the self-layered anti-corrosion hydrophilic coating after coating is 1-3 μm.

Citation Information

Patent Citations

  • Hydrophilic aluminum foil coating with integrated bottom and top and preparation method thereof

    CN102719188A

  • Graphene modified aluminum foil hydrophilic coating as well as preparation method and application method thereof

    CN105602376A

  • Anticorrosive hydrophilic coating containing chlorinated natural rubber, and preparation method thereof

    CN108395770A